2009
DOI: 10.1371/journal.pcbi.1000511
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Continuous-Time Dynamics of Energy and Fat Metabolism in Mice

Abstract: The mouse has become the most popular organism for investigating molecular mechanisms of body weight regulation. But understanding the physiological context by which a molecule exerts its effect on body weight requires knowledge of energy intake, energy expenditure, and fuel selection. Furthermore, measurements of these variables made at an isolated time point cannot explain why body weight has its present value since body weight is determined by the past history of energy and macronutrient imbalance. While fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 20 publications
5
66
0
Order By: Relevance
“…This beneficial increase in the antiathrerogenic fraction probably resulted from the monounsaturated oleic fatty acid content in pequi pulp and nut. Nevertheless, this effect of monounsaturated fat on HDL cholesterol is yet controversial since some studies have reported no effect on serum HDL-c levels due to the ingestion of monounsaturated fatty acids (GRUNDY; DENKE, 1990;PUIGGRÓS et al, 2002). However, many other studies have shown an increase in HDL-c (MATA et al, 1992;PÉREZ-JIMÉNEZ et al, 1995) corroborating the results of this study.…”
Section: Animals and Dietssupporting
confidence: 83%
“…This beneficial increase in the antiathrerogenic fraction probably resulted from the monounsaturated oleic fatty acid content in pequi pulp and nut. Nevertheless, this effect of monounsaturated fat on HDL cholesterol is yet controversial since some studies have reported no effect on serum HDL-c levels due to the ingestion of monounsaturated fatty acids (GRUNDY; DENKE, 1990;PUIGGRÓS et al, 2002). However, many other studies have shown an increase in HDL-c (MATA et al, 1992;PÉREZ-JIMÉNEZ et al, 1995) corroborating the results of this study.…”
Section: Animals and Dietssupporting
confidence: 83%
“…2d) or a significant decrease in daily energy expenditure ((EE); Supplementary Fig. 3) 12 , although both measures tended to deviate in the energy accumulative direction. Metabolic efficiency, that is, the percentage of consumed energy incorporated into fat, was substantially higher in the aP2-hCidea mice ( Fig.…”
Section: Resultsmentioning
confidence: 93%
“…However, there exist a wide variety of models describing the regulations of body weight and metabolism (see [9] and the references therein, [7,24]). These models, based mainly on ordinary differential equations, consider different mechanisms of regulation such as energy use in humans [6,23,24] or in rodents [18,19]. In humans, Horgan [24] described the regulation of body weight regulated only by itself and food intake with a discrete stochastic model and concluded that body weight remains around a fixed value if the mean food intake and physical activity are constant.…”
Section: Introductionmentioning
confidence: 99%
“…In [7], Chow and Hall studied the impact of stochastic fluctuations in food intake on body weight evolution and concluded that short-term fluctuations in food intake have a limited impact on body-weight. Guo and Hall [18,19] developed an ordinary differential equation model based on laws of energy conservation to predict changes in body weight and energy expenditure, using only energy intake, and applied this model to mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation